Application of multicriterion routing for increase of informative safety of komp’yuternykh networks - Мартынова, О. П.; Засядько A. A.; Баранов B. Л. (Problems of Informatization and Control, 2007)
It is suggested to promote informative safety of users of computer network by the multicriterion routing. The separate private criteria of quality of passing to information in acomputer network take into account not only descriptions of quality of passing to information, but along with them and criteria of quality of defence of the passed information ot an unauthorized division